Color-Tunable Indolizine-Based Fluorophores and Fluorescent pH Sensor - Taegwan Kim; Jonghoon Kim (Molecules, 2021)
A new fluorescent indolizine-based scaffold was developed using a straightforward synthetic scheme starting from a pyrrole ring. In this fluorescent system, an N,N-dimethylamino group in the aryl ring at the C-3 position of indolizine acted as an electron donor and played a crucial role in inducing a red shift in the emission wavelength based on the ICT process. Moreover, various electron-withdrawing groups, such as acetyl and aldehyde, were introduced at the C-7 position of indolizine, to tune and promote the red shift of the emission wavelength, resulting in a color range from blue to orange (462–580 nm). Furthermore, the ICT effect in indolizine fluorophores allowed the design and development of new fluorescent pH sensors of great potential in the field of fluorescence bioimaging and sensors.